IDENTIFICATION OF THE INFLUENCE OF ACADEMIC'S PERSONAL CHARACTERISTICS AND ACADEMIC'S PERCEIVED SUPPORT ON UNIVERSITY STUDENTS’ INTENTION TO BECOME TECHNOPRENEUR - Putri, Mediany Kriseka; Anggadwita, Grisna; Wicaksono, Mukti Bawono (Universitas Brawijaya, Indonesia, 2019)
Entrepreneurshipis one of the driving factors ofthe country's economy. More entrepreneurs meanmore potential for new business areas and thus more employment to grow. The development of industrial revolution 4.0 encourages entrepreneurs to be techno- logical entrepreneurs to face increasing competition. It is important for the university, an educational institution, to produce graduates who can compete in the era of Industry4.0 and provide solutions to state problems such as poverty and unemployment. Hence, measuring students' intention to become a technopreneur is necessary to see whether the university can prepare its students to become technopreneur who will be useful for the country and society. This study aims to measure the influence of factors in academic's personal characteristics and academic's perceived support on the university students' intention to become technopreneur.